2003
DOI: 10.1104/pp.103.020024
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Four β-Expansins (Zea m 1 Isoforms) from Maize Pollen  

Abstract: (P.A.B., C.V.).Four proteins with wall extension activity on grass cell walls were purified from maize (Zea mays) pollen by conventional column chromatography and high-performance liquid chromatography. Each is a basic glycoprotein (isoelectric point ϭ 9.1-9.5) of approximately 28 kD and was identified by immunoblot analysis as an isoform of Zea m 1, the major group 1 allergen of maize pollen and member of the ␤-expansin family. Four distinctive cDNAs for Zea m 1 were identified by cDNA library screening and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
113
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(124 citation statements)
references
References 53 publications
9
113
0
2
Order By: Relevance
“…This idea led Cosgrove and his colleagues to finally discover expansin proteins, which mediate acid wall extension without hydrolytic activity, from a series of plant walls (Cosgrove et al, 1997;Li, Z. C. et al, 1993;Li, L. C. et al, 2003;McQueen-Mason et al, 1992;Sampedro & Cosgrove, 2005). This study demonstrates that treating walls of C. cinerea with heating, protease or protein denaturants eliminated the acid-induced long-term wall extension activity of C. cinerea stipes exactly as seen in plant cell walls (Cosgrove, 1989), implying that this acid-induced stipe wall long-term extension is a proteinmediated process.…”
Section: Discussionmentioning
confidence: 99%
“…This idea led Cosgrove and his colleagues to finally discover expansin proteins, which mediate acid wall extension without hydrolytic activity, from a series of plant walls (Cosgrove et al, 1997;Li, Z. C. et al, 1993;Li, L. C. et al, 2003;McQueen-Mason et al, 1992;Sampedro & Cosgrove, 2005). This study demonstrates that treating walls of C. cinerea with heating, protease or protein denaturants eliminated the acid-induced long-term wall extension activity of C. cinerea stipes exactly as seen in plant cell walls (Cosgrove, 1989), implying that this acid-induced stipe wall long-term extension is a proteinmediated process.…”
Section: Discussionmentioning
confidence: 99%
“…5, clamped in a constant-force extensometer at 20-gram force in 50 mM sodium acetate (pH 5.5). Specimen length was recorded at 30-s intervals (23,36) before and after addition of recombinant EXLX1 or native EXPB1 purified from maize pollen (37).…”
Section: Methodsmentioning
confidence: 99%
“…S2A and Table III), class III peroxidase has been known as a heme-containing glycoprotein (42). Polygalacturonase, pollen-specific protein C13 (Os09g39950), ␤-expansin Os-EXPB13, and ␤-expansin have been well documented as pollen allergens (43)(44)(45). Previous investigations showed that most pollen allergens were glycoproteins, whereas glycan probably contributes to their allergenic activity (46).…”
Section: Identification Of Proteins Involved In Pollen Germinationmentioning
confidence: 99%